¿Hasta dónde llega la calle? Prácticas artísticas y espacio público - Raussert, Wilfried (Ensayos InterAmericanos, 2020)
Spurred by a new wave of protests around the world - from the Occupy movement, Black Lives Matter, the Arab Spring, and the various street marches against neoliberal governments throughout Latin America - Raussert examines how artistic practices in the Americas have challenged the control of public space in relation to gender, race, sexuality, class, and age in three periods (the 1920s and 1930s, the 1960s and 1970s, and the new millennium). This inter-American perspective sheds light on common utopian aspirations across time and space, as in the networked movements of indigenous, African-descended and the diasporic groups, epitomized by the Zapatista slogan: "Mientras los medios de comunicación sigan mintiendo, las paredes seguirán hablando" (As long as the media continues to lie, the walls will continue to talk). Indeed, this must-read book shows how contesting artists subvert the increasing privatization, consumerization and electronic monitoring of public space and its virtualization in the new media in our own time period. | George Yúdice (Professor of Latin American Studies and Modern Literature at the University of Miami, U.S.A.)